KONSEP WASATIAH QUR’ANI PERSPEKTIF TAFSÎR MAFÂTÎH AL-GAIB - Munawar, Aang (Journal of Comprehensive Science, 2025)
concept of Wasatiah Qur'ani from the perspective of the interpretation of Mafâtîh al-Gaib. The method used is a qualitative method which in interpretation theory is called the thematic method (Maudhû'i). The author collected all the data on the word wasath in the Qur'an and the characteristics of wasatiah, then analyzed it using the main source, namely the tafsîr book Mafâtîh al-Gaib, and presented it in this thesis. The conclusion of this thesis is that the word wasath and its derivation can be found in Q.S. al-Baqarah/2: 143, Q.S al-Baqarah/2: 238, Q.S. al-Qalam/68: 28. The meaning and interpretation of the word wasath in the tafsîr Mafâtîh al-Gaib in Q.S. al-Baqarah/2: 143 is fair, moderate and best. Meanwhile, in Q.S al-Baqarah/2: 238 the meaning and interpretation of the word wusthâ is middle. As for Q.S. al-Qalam/68: 28 meaning and interpretation of the word awsath is the best, fair, knowledgeable and ideal Meanwhile, the characteristics of Wasatiah which can be applied in everyday life by referring to Tafsîr Mafâtîh al-Gaib can be summarized into several important points, namely: first: Fairness and leaning towards goodness based on Q.S. al-Baqarah/2: 143, second: middle in terms of religion which includes: prohibition of insulting, insulting, insulting other beliefs or religions by encouraging speaking softly and full of wisdom to those who have not accepted the truth, this is based on Q.S. al-An'âm/6: 108, the prohibition on forcing people to enter into beliefs or religions is based on Q.S. al-Baqarah/2: 256, recommendations for respect and tolerance towards other religions (Q.S. al-Hujurât/49: 13), the ability to interact socially with non-Muslims, avoiding religious extremism (Q.S. al-Mumlahanah/60: 8), and third namely the prohibition of unjust/violent acts (Q.S. al-A'râf verse/7: 33).